The Athlete Food Choice Questionnaire (AFCQ): Validity and reliability in a sample of international high-performance athletes - Thurecht, R.; Pelly, F. E. (Medicine & Science in Sports & Exercise, 2021)
Purpose: The Athlete Food Choice Questionnaire (AFCQ) is a novel tool for understanding factors influencing athlete food selection and providing context to nutrition knowledge and diet quality data. Reliability, face, and content validity have been previously established during development. The aim of this study is to evaluate the AFCQ`s factorial structure, reliability, and construct validity in an independent sample of international high-performance athletes. Methods: The AFCQ contains 36 items within nine factors. Participants rate how frequently (1 never to 5 always) items influence their choices. Model consistency and construct validity was evaluated by confirmatory factor analysis. Measures included model fit incidences and duplicate methods examining reliability, convergent, and discriminant validity. Results: Athletes (n = 232) at the 2018 Commonwealth Games, Gold Coast, Australia, completed the AFCQ. A modified 32-item model achieved discriminant validity for all factors and convergent validity for "emotional influence," "food and health awareness," "nutritional attributes of food," "performance," and "influence of others." Reliability measures of all constructs except "usual eating practice" and "food values and beliefs" were above acceptable thresholds, although "usual eating practice" was considered tolerable and conditionally accepted. Conclusion: The AFCQ was confirmed in its original nine-factor structure in an independent sample of high-performance athletes. This provides a detailed and transparent account of the construct validity of the AFCQ, adding to the foundation of evidence for this new instrument. The AFCQ captures the unique influences specific to athletes while being broad enough for application across diverse sporting and culturally mixed cohorts. This tool could assist sports science professionals in making more informed and effective decisions around strategies to support athletes, including the ability to triage for specific sports nutrition advice.